Can Natural Zeolite Improve the Removal of Micropollutants in a Nitrifying Sequencing Batch Reactor? Insights on Bioreactor Performance, Kinetics, and Microbial Community Using Ibuprofen and Diclofenac as Model Micropollutants - Tello-Reyes, M (Elsevier Ltd, 2024)
This study presents the effect of natural zeolite (NZ) on a nitrifying sequencing batch reactor for removing ibuprofen (IBP) and diclofenac (DFC) in the long term, including kinetics and microbial community. The research was conducted in two 2 L liquid-volume bioreactors, one with 5 g/L of NZ. Nitrogen load rates ranging between 5.8 and 8.5 mg N/L h were studied. Bioreactors were operated for 217 days, with IBP and DFC concentrations ranging between 20 and 2000 μg/L. The results showed that using NZ in a nitrifying SBR only improves IBP removal at low concentrations (40 μg/L). IBP and DFC do not affect the nitrification efficiency or kinetic of ammonia removal. In the presence of IBP and DFC, NZ also favored a higher relative abundance in the genus Nitrosomonas and the Bradyrhizobiaceae family (responsible for nitrite-oxidizing activity), allowing higher IBP degradations at low IBP concentrations. Finally, IBP and DFC stimulated heterotrophic nitrification. © 2024 Elsevier Ltd
Keywords: DFC; IBP; Natural zeolite; Nitrification; SBR